Construction of microalgae polyculture based on key population analysis to improve biomass production in municipal wastewater. Issue 12 (3rd November 2022) - Liu, Weixing; Shang, Qingyu; Pan, Ting; Yan, Yixin; Singh, Rajendra Prasad; Fu, Dafang
Abstract : Paraburkholderia was identified as a key population, and a positive correlation was found between Nannochloropsis oceanica and Paraburkholderia . The microalgae culture experiments constructed based on them realized the improvement of productivity. Abstract : Previous studies revealed that microalgae polyculture in wastewater can improve productivity which is less expensive than bioaugmentation with bacteria. Keeping this in mind, the aim of the current study was to develop and validate a method for constructing a microalgae polyculture to improve biomass production based on bacterial community relationship analysis. Based on the differences in the utilization of nitrogen and phosphorus by a microalgae monoculture, four microalgae dual culture experiments were performed in simulated wastewater in the current work. The yield and quality of microalgae biomass and nitrogen and phosphorus consumption were measured. Compared with the monoculture, the average dry weight yield of the four microalgae dual cultures increased by 12.5%, reaching up to 58.3 mg L −1 d −1 . Results revealed that the combination of Pediastrum sp. and Micractinium sp. (PM) had the highest biofuel and biocrude yield under two conversion pathways of oil extraction and hydrothermal liquefaction, which was 15.8 and 17.5 mg L −1 d −1, respectively. With co-occurrence network analysis of bacterial communities, Paraburkholderia was identified as a key population that could further enhance the PM productivity. The second stage of the experiment was carried out through addition of the microalgae Nannochloropsis oceanica and Paraburkholderia on the basis of the PM. Compared with the PM, productivity was further improved in both groups. Based on the above findings, this study could provide different approaches about how to build highly productive microalgae polyculture systems.